EFFECTIVENESS OF CONTENT–BASED INSTRUCTION IN TEACHING READING (American Journal of Pedagogical and Educational Research, 2023)
The effectiveness of content-based instruction in teaching reading is examined in this article. The article's goal is to determine if content-based training is effective at teaching reading. The action research was to evaluate the benefits and drawbacks of content-based reading instruction. A post-test was given after the lesson had been finished. To ascertain if content-based instruction is effective in teaching reading, the outcomes of the two exams were compared. Reading instruction has been proven to be most successful when using content-based instruction.